(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This research aims to study and analyze the role of strategic learning in the strategic agility of a group of universities and private colleges in Baghdad by finding a solution to the main problem that was formulated with the main question (Was the senior management of private universities and colleges able to employ the dimensions of strategic learning in strategic agility?) as well. The research community included a number of universities and private colleges, while the research sample was intentional about the heads of scientific and administrative departments from these universities and private colleges It consists of (171) individuals, and data was collected through the use of questionnaires and relying on field visits and personal interviews with department heads. The data was also analyzed using the program (spss.v26). Several statistical methods were used, including the arithmetic mean, standard deviation, and coefficient of relative variation in order to measure the importance of differences between groups, the correlation coefficient (Pearson) to test the validity of the correlation hypotheses, and the regression coefficient to test the influence hypothesis. The research reached several results, the most prominent of which was the existence of a correlation relationship and a significant effect. Statistical significance for strategic learning (the independent variable) in strategic agility (the dependent variable).